Removal of ammonium-nitrogen (NH4-N) by micro flora in drain - Robiatun, Ismail (2008)
Nitrogen is a one of the important nutrient for aquatic plants and algae. Some of the nitrogen can get from the ammonium cation. However, if there are excessive of nutrients (contains nitrogen) it will stimulate the aquatic plant and algal growth. The uncontrolled release of nitrogen to the environment will cause to serious pollution problems. In order to prevent this problems become more serious, we should handled the nitrogen as a nutrient resource rather than a pollutant that only has to dispose off. Biological treatment is one of the potential treatment alternatives to reduce the nitrogen, where the nitrogen is used as nutrient to the microorganisms. In this study, the sequence batch reactor (SBR) system was used. Different organic loading rate (0.4, 1.3, 2.2, 3.1 and 4.0 mg/l/day) was studied in SBR system to compare the treatment efficiency in terms of water quality parameters (chemical oxygen demand, COD), suspended solid and the changes in NH -N concentration. The treated wastewater was analyzed for COD, NH 4 4 -N concentration and suspended solid by using HACH equipment. From this experiment the result shows that the organic loading rate to get maximum percentage COD reduction is 0.4 mg/l/day with 47.05% COD reduction and 124.13 mg/l suspended solid. Meanwhile the value of organic loading rate to get the maximum percentage concentration reduction is also 0.4 mg/l/day with 36.71% concentration reduction and 124.13 mg/l suspended solid. For maximum percentage COD reduction and maximum percentage concentration reduction the optimum value organic loading rate that need is 3.59 mg/l/day with 38% COD reduction, 24.9% concentration reduction and 208.49 mg/l suspended solid. All this results are base on Design of Expert. As a conclusion, this study showed that microflora in drain was efficient in removing the wastewater that contains ammonium-nitrogen.